The Concept of Jack Zipes’ Thoughts On Folktales - Widjati Hartiningtyas; Nur Wulan; Ida Nurul Chasanah (JENTERA: Jurnal Kajian Sastra, 2024)
Folktales are a form of folklore that reflects the values and social order that prevail in a community group in a certain period. To maintain the existence of folktales and transmit their cultural values, folktales have been adapted as children’s books. However, folktales undergo a lot of changes during the adaptation. The authors deliberately make the changes to eliminate the bad values in the folktales and make them educational reading for children. This article aims to analyze the adaptation process of Hikayat Maharaja Bikramasakti into a picture book entitled Ratna Komala and the Magic Rumbia Seed. Through close reading techniques, the researcher wrote the changes made to Hikayat Maharaja Bikramasakti when adapted into a picture book. Then, the researcher analyzed the data using Jack Zipes' thoughts. The research results show that the moral values prevailing in society and the government's ideology influence the adaptation of folklore. AbstrakCerita rakyat merupakan salah satu bentuk folklor yang mencerminkan nilai dan tatanan sosial yang berlaku dalam sebuah kelompok masyarakat dalam periode tertentu. Untuk menjaga eksistensi cerita rakyat serta mewariskan nilai-nilai budaya yang terkandung di dalamnya pada generasi mendatang, cerita rakyat diadaptasi menjadi bacaan bagi anak. Namun dalam proses adaptasi tersebut, cerita rakyat banyak mengalami perubahan. Perubahan itu dilakukan oleh penulis cerita adaptasi untuk menghilangkan nilai-nilai buruk cerita rakyat dan menjadikan cerita rakyat bacaan yang mendidik bagi anak. Artikel ini bertujuan menganalisis proses adaptasi Hikayat Maharaja Bikramasakti menjadi buku cerita bergambar yang berjudul Ratna Komala dan Biji Rumbia Ajaib. Melalui teknik pembacaan dekat, peneliti mencatat perubahan-perubahan yang terjadi pada cerita rakyat ketika diadaptasi menjadi buku cerita bergambar. Kemudian, peneliti menganalisis data tersebut menggunakan pemikiran Jack Zipes. Hasil penelitian menunjukkan bahwa nilai moral yang berlaku di masyarakat dan ideologi penguasa memengaruhi proses adaptasi cerita rakyat.